Bipolar ion exchange microsphere adsorption material as well as preparation method and application thereof

By simultaneously introducing quaternary ammonium-based functional groups and carboxylic functional groups into microsphere adsorption materials, the problem of being unable to simultaneously adsorption and separation of acidic and basic analytes in the prior art is solved, and the synchronous adsorption and separation of acidic and basic analytes is achieved, thereby improving the efficiency of biological detection.

CN119869487AActive Publication Date: 2025-04-25TIANJIN MEDICAL COLLEGE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510394271.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-25
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

The existing solid-phase extraction adsorbent materials cannot simultaneously adsorb and separate acidic and alkaline analytes, resulting in the need of two-step process for pretreatment in biological detection, which is inefficient.

Method used

A bisexual ion exchange microsphere adsorption material is developed to enhance the selective adsorption capacity of acidic and basic analytes by simultaneously introducing quaternary ammonium and carboxylic functional groups into the microspheres.

Benefits of technology

The synchronous adsorption and separation of acidic and alkaline analytes is achieved, and the efficiency of sample pretreatment and substance retention are improved, and it is suitable for the field of biological detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869487A_ABST
    Figure CN119869487A_ABST
Patent Text Reader

Abstract

The invention provides an amphiphilic ion exchange microsphere material as well as a preparation method and application thereof, and relates to the technical field of adsorption material preparation. The bipolar ion exchange microsphere adsorption material provided by the invention simultaneously contains a quaternary ammonium functional group and a carboxyl functional group, so that acidic and alkaline analytes in a sample can be synchronously and selectively retained; the proper pore-foaming agent, dispersing agent and initiator are matched for use, so that the surface of the microsphere material has a pore channel structure, the surface area of ion exchange is increased, and the adsorption capacity of the material is improved; due to charges attached to the surfaces of the microspheres and benzene ring structures contained in the microspheres, the amphiphilic ion exchange microsphere adsorption material provided by the invention also has hydrophilicity and lipophilicity and has a more comprehensive application range. And on the other hand, the preparation method of the bipolar ion microsphere exchange material provided by the invention is simple in process, mild in condition and beneficial to large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorption material preparation, and in particular to a zwitterionic ion exchange microsphere adsorption material and a preparation method and application thereof. Background Art

[0002] At present, solid phase extraction is a sample pretreatment technology widely used to enrich and separate analytes from complex samples. It can enrich analytes and eliminate matrix interference, so it is widely used in the sample pretreatment process of mass spectrometry detection. The core of solid phase extraction technology is adsorbent fillers, which often have high specific surface area hydrophilic and lipophilic properties or ion exchange properties. Most of the current adsorbents combine polymer skeletons and ion exchange groups to form mixed-mode adsorbents, namely reverse phase and ion exchange adsorption.

[0003] In the field of biological detection, it is often necessary to quantitatively analyze acidic analytes and alkaline analytes simultaneously. For example, 5-hydroxytryptamine and catecholamines are important neurotransmitters in the human body, and both are monoamine compounds, which are alkaline analytes. However, the metabolites of 5-hydroxytryptamine and some metabolites of catecholamines are compounds containing carboxyl groups, which are acidic analytes. At present, when detecting 5-hydroxytryptamine and its metabolites, catecholamines and their metabolites in urine, a two-step solid phase extraction method is usually used for pretreatment, that is, a filler containing a weak cationic group is first used to adsorb and separate the compounds containing amino groups, and then a filler containing a strong anionic group is replaced to adsorb and separate the compounds containing carboxyl groups. This is because most of the solid phase extraction fillers that have been commercialized on the market can only retain compounds containing one type of ionic group, and can only adsorb and separate acidic or alkaline analytes, and cannot retain acidic and alkaline analytes at the same time, and when extracting compounds with higher polarity, they have shown the problem of insufficient retention.

[0004] At present, there is no report on suitable solid phase extraction adsorption materials that can perform one-time adsorption separation of acidic and basic analytes. Therefore, it is very necessary to develop a solid phase extraction adsorption material that can simultaneously adsorb and separate acidic and basic analytes. Summary of the invention

[0005] The purpose of the present invention is to provide a zwitterionic ion exchange microsphere adsorption material and a preparation method and application thereof, so as to solve the technical problem that the solid phase extraction adsorption material in the prior art can only adsorb compounds of a single nature.

[0006] In order to solve the above technical problems, the present invention provides a zwitterionic ion exchange microsphere adsorption material, which contains a quaternary ammonium functional group and a carboxyl functional group; The structural formula of the microsphere adsorption material is as follows: .

[0007] Further, the density of the quaternary ammonium functional group is 0.5-2mmol / g; The density of the carboxyl functional group is 1-5 mmol / g.

[0008] The oxygen atom in the carboxyl functional group has a strong electron absorption capacity and is easy to transfer electrons with cations or positively charged groups in alkaline compounds to form a stable adsorption structure. The successful introduction of carboxyl functional groups into microsphere adsorption materials enhances the selective adsorption of compounds containing alkaline functional groups in analytes.

[0009] The quaternary ammonium functional group contains a nitrogen atom, has a pair of lone pairs of electrons, is completely ionized in the solution and carries a positive charge, and can selectively retain acidic substances. The present application creatively introduces carboxyl and quaternary ammonium functional groups into the microsphere adsorption material at the same time, thereby increasing the application scope of the microsphere adsorption material and realizing the simultaneous adsorption of acidic and alkaline substances.

[0010] Further, the particle size of the microsphere adsorption material is 10μm -300μm; The pore size of the microsphere adsorption material is 1 nm-50 nm.

[0011] The surface of the microspheres contains a pore structure, which increases the specific surface area of ​​the material and ensures sufficient contact between the analyte and the microsphere adsorption material.

[0012] The present invention also provides a method for preparing the microsphere adsorption material, the specific steps of which are as follows: Step 1, adding a dispersant to distilled water, stirring thoroughly to obtain a dispersant aqueous solution with a concentration of 0.1%-20%; the concentration of the dispersant aqueous solution is preferably 3%-10%; The dispersant is hydroxypropyl methylcellulose and / or polyvinyl alcohol.

[0013] Dispersants have excellent dispersing ability. Appropriate dispersants can help monomers form stable and uniform droplets and control the collision of particles after polymerization, keeping them in a stable state.

[0014] Step 2, weighing 50-90 parts of a polymer monomer mixture, 1-90 parts of a porogen, and 0.01-1 parts of an initiator according to their mass fractions, and stirring them thoroughly to obtain 100 parts of an oil phase mixture; The polymer monomer mixture includes a first monomer and a second monomer; The first monomer is selected from o-divinylbenzene, m-divinylbenzene, and p-divinylbenzene; The second monomer is selected from p-chloromethylstyrene and 4-chlorostyrene.

[0015] The polymer monomer contains a benzene ring and is lipophilic, which is beneficial to improving the adsorption effect on hydrophobic substances.

[0016] Step 3, fully mixing the acrylic acid ester monomer with the oil phase mixture and the dispersant aqueous solution, and reacting under condensation reflux at 50-80° C. for 4-20 hours; after the reaction, cooling to room temperature, washing with water and ethanol in turn, and drying at 60° C. to obtain a first reaction product; The acrylic acid ester monomer is selected from methyl acrylate, methyl methacrylate, and ethyl methacrylate; The added mass of the acrylic ester monomer is 1%-20% of the polymer monomer mixture; preferably 8%-15%; The mass ratio of the oil phase mixture to the dispersant aqueous solution is (30-60):100.

[0017] Step 4, placing the first reaction product in a toluene solution and swelling it for 0.5-1.5 hours to obtain a swollen mixture; Adding a tertiary amine monomer to the swelling mixture, and continuing to fully stir at 80-90° C. to carry out a polymerization reaction for 4-20 hours to obtain a second reaction product; The tertiary amine monomer is selected from N,N-dimethylbutylamine, trimethylamine, and triethylamine; The added amount of the tertiary amine monomer is 1-10 times the mass of the second monomer, preferably 6-8 times.

[0018] Step 5, adding 100 parts of alkaline methanol solution to the second reaction product, stirring at a low speed at 65-75° C., and performing ester hydrolysis reaction for 20-30 hours; after the reaction is completed, cooling to room temperature, washing with ethanol, sodium bicarbonate solution, and water in turn, and drying to obtain the zwitterionic ion exchange microsphere adsorption material.

[0019] After the quaternary ammonium functional group is grafted, an ester hydrolysis reaction is performed so that the ester group grafted onto the microsphere in step 3 is hydrolyzed in an alkaline environment to obtain a carboxyl functional group, and finally a weak cation-strong anion zwitterionic ion exchange microsphere having both a carboxyl functional group and a quaternary ammonium functional group is obtained.

[0020] The microsphere adsorption material is a weak cation-strong anion exchange microsphere. The surface of the microsphere is attached with electric charge and has hydrophilic properties, which is beneficial to improve the adsorption effect of hydrophilic substances. Furthermore, the dispersant in step 1 is hydroxypropyl methylcellulose and / or polyvinyl alcohol.

[0021] Furthermore, in step 2, the mass ratio of the first monomer to the second monomer is 1:(1-3).

[0022] Preferably, the porogen in step 2 is a mixture of one or more of dichloromethane, n-dodecane, toluene, o-dichlorobenzene, and liquid paraffin; The initiator is azobisisobutyronitrile and / or benzoyl peroxide.

[0023] Preferably, in step 2, the mass ratio of the first monomer: the second monomer: the porogen: the initiator is (17-30): (34-60): (9-50): (0.01-1).

[0024] Furthermore, the specific steps of fully mixing in step 3 are: adding the acrylic acid ester monomer and the oil phase mixture into the dispersant aqueous solution and stirring evenly; Alternatively, the oil phase mixture is first added to the dispersant aqueous solution, and then the acrylic acid ester monomer is added at 50-80° C. and mixed evenly.

[0025] Furthermore, the stirring rate in step 1 and step 2 is 200-500 r / min; Appropriate stirring rate can promote the dispersion of the oil phase into small droplets during the mixing process.

[0026] The rate of low-speed stirring in step 5 is 80-120 r / min.

[0027] Preferably, the alkaline methanol solution in step 5 is selected from KOH-methanol solution and NaOH-methanol solution, and more preferably KOH-methanol solution; The concentration of the alkaline methanol solution is 3%wt-5%wt.

[0028] On the other hand, the present invention also provides a solid phase extraction device for synchronously separating acidic and basic analytes, which uses the above-mentioned zwitterionic ion exchange microsphere adsorption material or the zwitterionic ion exchange microsphere adsorption material prepared by the above-mentioned method as filler.

[0029] By adopting the above technical solution, the present invention has the following beneficial effects: The present invention provides a zwitterionic ion exchange microsphere material, which creatively introduces carboxyl functional groups and quaternary ammonium functional groups into the microsphere adsorption material at the same time, and can selectively retain acidic and alkaline analytes in the sample simultaneously; through the use of appropriate porogens, dispersants and initiators, the surface of the microsphere material has a pore structure, which increases the surface area of ​​ion exchange and improves the adsorption capacity of the material; the charges attached to the surface of the microspheres and the benzene ring structure contained in the microspheres themselves make the zwitterionic ion exchange microsphere adsorption material provided by the present invention also have hydrophilicity and lipophilicity, and have a more comprehensive scope of application. On the other hand, the preparation method of the zwitterionic microsphere exchange material provided by the present invention has a simple process, mild conditions, and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 A scanning electron microscope image of the zwitterionic ion exchange microsphere adsorption material provided by the present invention; Figure 2 A particle size distribution diagram of the zwitterionic ion exchange microsphere adsorption material provided by the present invention; Figure 3 It is the nitrogen adsorption-desorption isotherm curve of the microsphere adsorption material; Figure 4 (a) is a scanning electron micrograph of zwitterionic ion exchange microspheres prepared using hydroxypropyl methylcellulose as a dispersant; Figure 4 (b) is a scanning electron micrograph of zwitterionic ion exchange microspheres prepared using 3% by mass of polyvinyl alcohol as a dispersant; Figure 4 (c) is a scanning electron micrograph of zwitterionic ion exchange microspheres prepared using 5% by mass of polyvinyl alcohol as a dispersant; Figure 4 (d) is a scanning electron micrograph of zwitterionic ion exchange microspheres prepared using 10% by mass of polyvinyl alcohol as a dispersant; Figure 5 (a) is a scanning electron micrograph of zwitterionic ion exchange microspheres prepared using dibenzoyl peroxide as an initiator; Figure 5 (b) is a scanning electron micrograph of zwitterionic ion exchange microspheres prepared using azobisisobutyronitrile as an initiator; Figure 6 (a) is a scanning electron microscope image of the zwitterionic ion exchange microspheres obtained when the stirring rate is 250 r / min; Figure 6 (b) is a scanning electron micrograph of the zwitterionic ion exchange microspheres obtained when the stirring rate is 300 r / min; Figure 6 (c) is a scanning electron micrograph of the zwitterionic ion exchange microspheres obtained when the stirring rate is 350 r / min; Figure 6 (d) is a scanning electron micrograph of the zwitterionic ion exchange microspheres obtained when the stirring rate is 400 r / min; Figure 7The curve diagram of the reaction yield versus reaction time in Example 9; Figure 8 This is a scanning electron microscope image of the zwitterionic ion exchange microspheres obtained by the preparation method provided in Example 10; Fig. 9 This is a schematic diagram of the selective adsorption principle of the zwitterionic ion exchange microsphere adsorption material provided by the present invention. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The present invention is further explained below in conjunction with specific implementation modes.

[0034] The preparation method of the zwitterionic ion exchange microsphere adsorption material provided by the present invention is as follows, and the specific steps are: Step 1, adding a dispersant to distilled water, stirring at a rate of 200-500 r / min to obtain a dispersant aqueous solution with a concentration of 0.1%-20%; The dispersant is hydroxypropyl methylcellulose and / or polyvinyl alcohol; Step 2, weighing 50-90 parts of a polymer monomer mixture, 1-90 parts of a porogen, and 0.01-1 parts of an initiator, and stirring at a rate of 200-500 r / min to obtain an oil phase mixture; The polymer monomer mixture includes a first monomer and a second monomer; the molar ratio of the first monomer to the second monomer is 1:(1-3); The first monomer is selected from o-divinylbenzene, m-divinylbenzene, and p-divinylbenzene; The second monomer is selected from p-chloromethylstyrene and 4-chlorostyrene; The porogen is a mixture of one or more of dichloromethane, n-dodecane, toluene, o-dichlorobenzene, and liquid paraffin; The initiator is azobisisobutyronitrile and / or benzoyl peroxide; Step 3, fully mixing the acrylic acid ester monomer, the oil phase mixture and the dispersant aqueous solution, and reacting them under condensation reflux at 50-80° C. for 4-20 hours. After the reaction is completed, cooling to room temperature, washing with water and ethanol in turn, and drying at 60° C. for 10-12 hours to obtain a first reaction product; The acrylic acid ester monomer is selected from methyl acrylate, methyl methacrylate, and ethyl methacrylate; The amount of the acrylic ester monomer added is 1%-20% of the mass of the polymer monomer mixture; Step 4, placing the first reactant in a toluene solution and swelling it for 0.5-1.5 hours to obtain a swollen mixture; Adding a tertiary amine monomer to the swelling mixture, and continuing to fully stir at 80-90° C. for 4-20 hours to obtain a second reactant; The tertiary amine monomer is selected from N,N-dimethylbutylamine, trimethylamine, and triethylamine; The added amount of the tertiary amine monomer is 1-10 times the mass of the second monomer.

[0035] Step 5, adding a 3%wt-5%wt alkaline methanol solution to the second reaction product, stirring at 65-75°C at a rate of 80-120r / min, and performing an ester hydrolysis reaction for 20-30h; after the reaction is completed, cooling to room temperature, washing with ethanol, sodium bicarbonate solution, and water in turn, and drying at 60°C for 10-12h to obtain the zwitterionic ion exchange microsphere adsorption material; The above components are all calculated by mass.

[0036] Method for observing the morphology of microsphere materials: The surface of the microsphere adsorption material is sprayed with gold; then it is baked with an infrared lamp for 20 minutes, and then the material is placed in the sample chamber and evacuated; the morphology and surface state of the microsphere material under a scanning electron microscope are as follows Figure 1 shown.

[0037] Method for determining the particle size of microsphere materials: Ultrasonic dispersion of an appropriate amount of microspheres in a mixed liquid of water and ethanol; Then take an appropriate amount of the mixed liquid and use MS3000 micron particle size analyzer to further determine the particle size distribution range, such as Figure 2 shown.

[0038] Method for determining the pore size of microsphere materials: The microsphere material is heated and vacuumed to degas to remove substances adsorbed on the surface; Then weigh it and put it into liquid nitrogen. Use V-Sorb280OTP fully automatic specific surface area and pore size analyzer to calculate the high pressure and absorption of the test sample according to the specified different pressure points to obtain the following Figure 3 The adsorption isotherm curve is shown in Figure 2. The specific surface area, pore size and pore size distribution range are calculated through the adsorption isotherm, and the average pore size of the microsphere material is calculated through the Barrett-Joyner-Halendamethod model.

[0039] Determination method of carboxyl and quaternary ammonium functional group density: (1) Calibration of sodium hydroxide solution: first take a certain amount of potassium hydrogen phthalate into a beaker, dry it at 105-110℃ for 2-3h, and set aside.

[0040] Blank: Take 50 ml of deionized water and titrate with sodium hydroxide solution. Determine three times in parallel and take the average value Vblank. The titration endpoint pH is 9.0-9.1.

[0041] Calibration: Weigh 0.5000g potassium hydrogen phthalate, dissolve it in 50 ml deionized water, and titrate with the sodium hydroxide solution to be tested. The titration end point pH is 9.0-9.1. Determine three times in parallel and take the average value V1. Calculate according to the following formula to obtain the calibration concentration of the sodium hydroxide solution: .

[0042] (2) Calibration of hydrochloric acid solution: Use a pipette to accurately transfer 25 ml of the hydrochloric acid solution to be tested into a conical flask, add 25 ml of deionized water, and titrate with a calibrated sodium hydroxide solution. The titration end point pH is 7.0. Perform three parallel determinations and take the average value V2. Calculate the calibrated concentration of the hydrochloric acid solution according to the following formula: .

[0043] (3) Determination of carboxyl content of samples: Titration experiment: Weigh 0.5000g / 1.0000g of the microsphere adsorption material provided by the present invention into a conical flask, add 100 ml of 0.1mol / L sodium hydroxide solution, shake well, seal, place in a 40°C water bath, soak for 2 hours, take out, and cool to room temperature. Use a pipette to transfer 25 ml of the supernatant, add it to 25 ml of deionized water, and titrate with a calibrated hydrochloric acid solution. The indicator indicates the end point, and the metering point pH is 7. Titrate three times in parallel and take the average value V3.

[0044] Blank experiment: Weigh 0.5000g / 1.0000g of the microsphere adsorption material precursor provided by the present invention into a conical flask, add 100 ml of 0.1mol / L sodium hydroxide solution, shake well, seal, place in a 40°C water bath, soak for 2 hours, take out, and cool to room temperature. Use a pipette to accurately transfer 25 ml of 0.1mol / L sodium hydroxide solution, add 25 ml of deionized water, and then titrate with a calibrated hydrochloric acid solution. The indicator indicates the end point, and the metering point pH is 7. Titrate three times in parallel and take the average value V4. According to the volume of hydrochloric acid consumed, calculate according to the following formula to obtain the carboxyl content W (carboxyl) of the microspheres: .

[0045] (4) Determination of quaternary ammonium content of samples: Ø Titration experiment: Weigh 0.5000g / 1.0000g of the microsphere adsorption material provided by the present invention into a conical flask, add 100 ml of 0.1mol / L hydrochloric acid solution, shake well, seal, place in a 40°C water bath, soak for 2 hours, take out, and cool to room temperature. Use a pipette to transfer 25 ml of the supernatant into a conical flask, add 25 ml of deionized water, and titrate with a calibrated sodium hydroxide solution. The indicator indicates the end point, and the metering point pH is 7. Titrate three times in parallel and take the average value V5.

[0046] ØBlank experiment: Weigh 0.5000g / 1.0000g of the microsphere adsorption material precursor provided by the present invention into a conical flask, add 100 ml of 0.1mol / L hydrochloric acid solution, shake well, seal, place in a 40°C water bath, soak for 2 hours, take out, and cool to room temperature. Use a pipette to accurately transfer 25 ml of 0.1mol / L hydrochloric acid solution, add 25 ml of deionized water, and titrate with a calibrated sodium hydroxide solution. The indicator indicates the end point, and the metering point pH is 7. Titrate three times in parallel and take the average value V6. According to the volume of sodium hydroxide consumed, calculate according to the following formula to obtain the quaternary ammonium content W (quaternary ammonium group) of the microspheres; .

[0047] Example 1

[0048] According to the method provided by the present invention, amphoteric ion exchange microsphere adsorption material is prepared.

[0049] Step 1, add 6g of polyvinyl alcohol into 120ml of distilled water, stir thoroughly at a rate of 350r / min to obtain a dispersant aqueous solution for standby use; Step 2, weigh 6.7 g of o-divinylbenzene, 20.1 g of p-chloromethylstyrene, 20 ml of toluene, and 0.1848 g of azobisisobutyronitrile, and stir at a rate of 350 r / min for 30 min to obtain an oil phase mixture for standby use; Step 3, fully mixing the oil phase mixture obtained in step 2 with the dispersant aqueous solution obtained in step 1, stirring at a rate of 350 r / min for 30 min; adding 2.5 ml of methyl methacrylate at 70° C., condensing and refluxing for 12 h; after the reaction is completed, cooling to room temperature, washing with water and ethanol in turn, and drying at 60° C. for 12 h to obtain a first reactant; Step 4, taking 2 g of the first reactant obtained in step 3 and placing it in 20 ml of toluene solution, swelling it for 1 hour, and obtaining a swollen mixture; adding 12.5 ml of N,N-dimethylbutylamine, stirring at 85° C. and 350 r / min for 18 hours, and obtaining a second reactant after the reaction is completed; Step 5, cooling the second reactant obtained in step 4 to 70°C; adding 100 ml of a 4% KOH-methanol solution under low-speed stirring at 100 r / min, and reacting for 24 hours; after the reaction is completed, cooling to room temperature, washing the product with ethanol, sodium bicarbonate solution, and water, respectively, and vacuum drying at 60°C for 12 hours to obtain a zwitterionic ion exchange microsphere adsorption material; It was determined that the zwitterionic ion exchange microsphere adsorption material obtained in this example had a maximum pore diameter of 2.3525 nm, a particle size of 30 μm-60 μm, a span value of 0.757, a carboxyl density of 4.8972 mmol / g, and a quaternary ammonium density of 1.3564 mmol / g.

[0050] Example 2

[0051] This example verifies the effect of the type and amount of porogen added on the pore size of zwitterionic ion exchange microspheres.

[0052] The preparation conditions of this embodiment are basically the same as those of embodiment 1, except that different types and different addition amounts of porogens are used in step 2 to obtain 6 groups of zwitterionic ion exchange microsphere materials. The specific conditions for using each group of porogens are shown in Table 1: Table 1 The ratios and addition ratios of the 6 groups of different porogens in Example 2 are as follows

[0053] The pore sizes of the six groups of zwitterionic ion exchange microsphere adsorbent materials obtained in this example were measured using a V-Sorb280OTP fully automatic specific surface area and pore size analyzer. The results are shown in Table 2: Table 2 The pore size measurement results of 6 groups of microsphere materials obtained in this example

[0054] As can be seen from Table 2, when the porogen contains n-dodecane or liquid paraffin, the pore size of the obtained zwitterionic ion exchange microspheres is significantly larger; after appropriately adding toluene, dichloromethane, and o-dichlorobenzene, the pore size of the obtained zwitterionic ion exchange microspheres is reduced to varying degrees; as mentioned above, when only toluene and dichloromethane are used as porogens in the sample preparation process of Examples 2-6, the pore size of the obtained zwitterionic ion exchange microspheres can be reduced to less than 10nm. For microsphere adsorption materials, the smaller the pore size, the larger the specific surface area of ​​the material, the more grafted carboxyl and quaternary ammonium functional groups, and the greater the adsorption amount of the microsphere material. In actual use, different types of porogens can be selected as needed to adjust the pore size of the obtained zwitterionic ion exchange microspheres. However, considering that when the pore size is too large, impurities such as macromolecular proteins may be adsorbed, resulting in a decrease in the specificity of the zwitterionic ion exchange microspheres, the pore size of the zwitterionic ion exchange microspheres provided by the present invention is preferably 1nm-50nm.

[0055] Example 3

[0056] like Figure 4 (a)- Figure 4 As shown in (d), this example verifies the effect of the type and proportion of dispersant added on the particle size of zwitterionic ion exchange microspheres.

[0057] The preparation process of this embodiment is basically the same as that of Example 1, except that in step 1, aqueous solutions of 5% hydroxypropyl methylcellulose, 3% polyvinyl alcohol, 5% polyvinyl alcohol, and 10% polyvinyl alcohol are prepared as dispersants, respectively, to prepare 4 groups of zwitterionic ion exchange microspheres. The particle size distribution ranges of the 4 groups of microsphere samples are measured by using an MS3000 micron particle size analyzer as shown in Table 3: Table 3 The results of the particle size range determination of the four groups of zwitterionic ion exchange microspheres obtained in this example

[0058] like Figure 4 As shown in (a), the microspheres obtained by using hydroxypropyl methylcellulose as a dispersant under a scanning electron microscope show uneven particle size distribution, complex morphology and large fragments. Figure 4 (b)- Figure 4 (d) and the data in Table 3 show that the microspheres obtained by using polyvinyl alcohol as a dispersant have uniform particle size distribution and no fragmentation; the particle size is significantly correlated with the concentration of added polyvinyl alcohol. In the preparation method of the zwitterionic ion exchange microspheres provided by the present invention, the dispersant is preferably polyvinyl alcohol, and the concentration is 0.1%-20%, more preferably 3-10%.

[0059] Example 4

[0060] like Figure 5 (a)- Figure 5 As shown in (b), this example verifies the effect of adding different types of initiators on the structure of the prepared zwitterionic ion exchange microspheres.

[0061] The preparation process of this embodiment is basically the same as that of embodiment 1, except that in step 2, dibenzoyl peroxide is used as an initiator to prepare the zwitterionic ion exchange microspheres.

[0062] Under an electron microscope, it can be clearly seen that Figure 5 As shown in (a), the amphoteric ion exchange microspheres prepared by using dibenzoyl peroxide as an initiator in Example 4 have uneven particle size distribution, rough surface, and broken depressions; Figure 5As shown in (b), the particle size distribution of the zwitterionic ion exchange microspheres prepared by using azobisisobutyronitrile as an initiator in Example 1 is uniform between 30 μm and 60 μm, and the surface is smooth without depressions. This may be due to the fact that the polymerization temperature is 70°C, and the decomposition rate of azobisisobutyronitrile at 70°C is significantly faster than that of dibenzoyl peroxide, and the resulting microspheres are more rounded. Therefore, in the preparation method of zwitterionic microspheres provided by the present invention, the initiator is preferably azobisisobutyronitrile.

[0063] Example 5

[0064] like Figure 6 (a)- Figure 6 As shown in (d), this example verifies the effect of stirring rate on the particle size of zwitterionic ion exchange microspheres.

[0065] The preparation process of this embodiment is basically the same as that of embodiment 1, except that the stirring rates in the sufficient stirring process described in step 1 and step 2 are 250 r / min, 300 r / min, and 400 r / min, respectively, to prepare three groups of zwitterionic ion exchange microspheres. Figure 6 As shown in (a), when stirring at a low speed of 250 r / min, the circulation flow of the system is weak and the shear force is insufficient, resulting in uneven particle size distribution of the obtained microspheres; Figure 6 As shown in (b), when the stirring speed is 300 r / min, the large droplets break up under high-speed shear conditions, and the resulting microspheres are more regular in morphology. However, due to insufficient shear force, some of the microspheres still have adhesion. When the stirring rate reaches 350 r / min, as shown in Figure 6 As shown in (c), the particle size of the microspheres obtained in Example 1 is between 30 μm and 60 μm, with regular shape and uniform distribution; and as the stirring speed is further increased to 400 r / min, as shown in Figure 6 As shown in (d), too much shear force results in a smaller particle size of the obtained microspheres, an uneven morphology, and fragmentation. Therefore, the stirring rate in step 1 and step 2 of the preparation method of zwitterionic ion exchange microspheres provided by the present invention is 200-500 r / min, preferably 350 r / min.

[0066] Example 6

[0067] This example verifies the effects of different acrylic acid ester monomers and their addition amounts on the functional group density in the obtained zwitterionic ion exchange microspheres.

[0068] The preparation process in this embodiment is basically the same as that in Embodiment 1, except that the type and amount of acrylic acid ester monomer added in step 3 are as shown in Table 4: Table 4 Comparison of sample preparation conditions in each group in this example

[0069] The functional group density of the six groups of zwitterionic ion exchange microspheres obtained in this example was measured and is shown in Table 5: Table 5 Determination results of functional group density of 6 groups of microspheres obtained in this example

[0070] It can be seen from the measurement results in Table 5 that with the increase in the amount of acrylate monomer added, the carboxyl density in the obtained zwitterionic ion exchange microspheres continues to increase. This is because when the amount of monomer added is small, the active sites of the vinyl in the microspheres are sufficient, so that the carboxyl density of the obtained microspheres increases with the increase in the amount of acrylate monomer added; when the amount added reaches 8% of the total mass of the polymer monomer mixture, the grafting active sites in the microspheres tend to be saturated, and the number of ester bonds that complete the grafting also tends to be stable, which is finally manifested as the measured carboxyl density The growth trend is gradually flat and close to saturation. On the other hand, due to the difference in molecular structure, under the premise of the same addition ratio, the carboxyl density of the zwitterionic ion exchange microspheres obtained by adding methyl methacrylate in the embodiment is higher. Therefore, in the preparation method provided by the present invention, for the acrylate monomer, methyl methacrylate is preferably used, and the addition ratio is preferably 8%-15% of the total mass of the polymer monomer mixture.

[0071] Example 7

[0072] This example verifies the effect of the type and ratio of tertiary amine monomers added on the density of quaternary ammonium groups in the resulting zwitterionic ion exchange microspheres.

[0073] The preparation conditions provided in this embodiment are basically the same as those in Example 1, except that in step 4, three different tertiary amine monomers are added respectively, and the added amounts are shown in Table 6: Table 6 Specific conditions for adding tertiary amine monomers in this example

[0074] The functional group density of the six groups of zwitterionic ion exchange microspheres prepared in this example was measured and is shown in Table 7: Table 7 Determination results of functional group density of microspheres obtained in each group in this example

[0075] Based on the measured data in Table 7, it can be seen that with the continuous increase in the amount of tertiary amine monomer added, the quaternary ammonium group density of the obtained zwitterionic ion exchange microspheres also gradually increases; when the amount of tertiary amine monomer added reaches 8 times the total mass of the second monomer added, the quaternary ammonium group density of the obtained microspheres no longer increases significantly, which may be because the active sites suitable for quaternary ammonium functional group grafting in the microsphere material are saturated at this time. Therefore, in the preparation method provided by the present invention, the amount of tertiary amine monomer added is preferably 1-10 times the total mass of the second monomer, and preferably 6-8 times from an economic point of view.

[0076] Example 8

[0077] In this embodiment, different zwitterionic ion exchange microsphere materials are obtained by adjusting the total mass of the polymer monomer mixture.

[0078] The preparation conditions of this embodiment are basically the same as those of embodiment 1, except that the addition masses of o-divinylbenzene and p-chloromethylstyrene in step 2 are respectively adopted in two schemes as shown in Table 8: Table 8 Addition scheme of o-divinylbenzene and p-chloromethylstyrene in this example

[0079] The two groups of zwitterionic ion exchange microspheres obtained were labeled as Example 8-1 and Example 8-2, respectively.

[0080] Example 9

[0081] like Figure 7 As shown, this example verifies the effect of polymerization reaction time on reaction yield.

[0082] The preparation conditions of this example are basically the same as those of Example 1, except that the stirring reaction time in step 4 is 4 h, 8 h, 12 h, 16 h, and 20 h, respectively, to obtain 5 groups of zwitterionic ion exchange microspheres, each group is repeated 3 times, and the average yield is calculated 3 times to obtain a curve of yield versus reaction time, as shown in FIG. Figure 7 As shown. Before the reaction time reaches 12h, the reaction yield increases with the increase of reaction time, and when the reaction time reaches 12h, the yield reaches 84.6%; when the reaction time exceeds 12h, the reaction yield remains stable, and even due to being at high temperature for too long, the yield decreases slightly. After 20h of reaction, the yield is 81.3%, and the relative standard deviation is 2.55%. Therefore, in the preparation method of the zwitterionic ion exchange microspheres provided by the present invention, the polymerization reaction time is preferably 12h.

[0083] Example 10

[0084] like Figure 8 As shown, this example verifies the effect of the step of adding acrylic ester monomers on the structure of zwitterionic ion exchange microspheres.

[0085] The preparation process of this embodiment is basically the same as that of Example 1, except that, in step 3, 2.5 ml of methyl methacrylate and the oil phase mixture obtained in step 2 are added to the dispersant aqueous solution obtained in step 1 and mixed thoroughly, stirred at a rate of 350 r / min, and condensed and refluxed for 12-16 hours; after the reaction is completed, it is cooled to room temperature, washed with water and ethanol in turn, and dried at 60°C for 12 hours to obtain the first reactant.

[0086] The zwitterionic ion exchange microspheres obtained in this example were observed under a scanning electron microscope. Figure 8 As shown, the microspheres generated by the reaction have a large number of microspheres aggregated together, the dispersibility is poor, and the microspheres have different particle sizes, which are significantly different from the morphology of the microspheres obtained in Example 1. The above phenomenon occurs because the addition of acrylate monomers together with the oil phase mixture will accelerate the polymerization reaction, resulting in the generation of a large number of microspheres in a short period of time, adhesion, and the complex morphology of the final reaction product. Therefore, the step of adding acrylate monomers in the preparation method of zwitterionic ion exchange microspheres provided by the present invention is preferably to first fully mix the oil phase mixture with the dispersant aqueous solution, and then add the acrylate monomers at 50-80°C and mix them evenly.

[0087] Experimental Example 1 This experimental example verifies the recovery rate of polar and non-polar analytes by the zwitterionic ion exchange microspheres obtained in the present invention.

[0088] Step S1, weighing appropriate amounts of non-polar analyte docetaxel and polar analyte ranitidine respectively, dissolving them in methanol and preparing them into 1 g / L standard stock solutions respectively; then taking appropriate amounts of the two standard stock solutions respectively to prepare 10 mg / L mixed standard working solutions; Step S2, selecting samples Example 6-1, Example 6-4, Example 7-1, Example 7-5, Example 8-1, and Example 8-2 from the zwitterionic ion exchange microsphere samples prepared in Example 6 to Example 8 as fillers in the solid phase extraction process, and accurately weighing 20 mg of the above six groups of samples respectively, and placing them in 6 1 mL solid phase extraction columns with sieve plates at both ends; Step S3, first activate with 500 μL of methanol, then balance the solid phase extraction material with 500 μL of deionized water, take 1 mL of the mixed standard solution described in step S1 and pass it through the solid phase extraction column, control the sample flow rate to 5 mL / min, wash the solid phase extraction column with 1 mL of 50% acetonitrile aqueous solution after passing through the column, then elute the solid phase extraction column with the eluent, and then elute the solid phase extraction column twice with 1 ml of deionized water to obtain 6 groups of eluents; blow the above eluents to nearly dryness with a nitrogen blower, and then dilute to 1 mL with methanol, and do three groups in parallel; Step S4, using ultra-high performance liquid chromatography technology for machine detection, using 0.1% (v / v) formic acid aqueous solution and methanol as mobile phases for gradient elution, the elution gradient is: 0-5min 2% methanol; 5-10min 60% methanol; 10-13min 100% methanol; 13-15min 100% methanol; 15-18min 2% methanol, and quantification is performed using the external standard method.

[0089] (5) The recoveries of docetaxel and ranitidine were calculated by peak area as shown in Table 9: Table 9 The recovery results of each group of samples for docetaxel and ranitidine described in this example

[0090] Since it contains both lipophilic benzene rings and hydrophilic charges attached to the surface, the zwitterionic ion exchange microsphere material provided by the present invention is used as a filler, and polar analytes and non-polar analytes can be extracted and separated efficiently during the solid phase extraction process. As shown in Table 9, the recovery rates of polar analytes in Example 6-1 and Example 7-1 are relatively low. This is because the density of carboxyl and quaternary ammonium functional groups contained in these two groups of microsphere materials is relatively low, and the charges attached to the surface are relatively small, resulting in poor hydrophilicity compared to other groups; with the increase in the density of carboxyl and quaternary ammonium functional groups, the recovery rate of polar analytes by the microsphere material is significantly improved. The recovery rate of polar analytes prepared by the zwitterionic ion exchange microspheres of Example 7-5 can reach 99.0%; while Examples 8-1 and 8-2 show significant The adsorption effect of the zwitterionic ion exchange microspheres obtained in Example 8-2 was particularly good, and the recovery rate of docetaxel reached 96.1%. This shows that the more the total amount of the polymer monomer mixture in step 2 of the preparation method provided by the present invention, the more benzene rings the zwitterionic ion exchange microspheres finally generated by the reaction contain, the stronger the lipophilicity, and the better the adsorption effect on non-polar analytes; on the other hand, the increase in the total amount of monomers also increases the grafting sites of carboxyl and quaternary ammonium functional groups, so the density of carboxyl and quaternary ammonium functional groups is also increased, and the recovery rate of polar analytes is also improved.

[0091] Experimental Example 2 This experimental example verifies that the zwitterionic ion exchange microsphere material provided by the present invention can achieve synchronous solid phase extraction separation of acidic analytes and basic analytes.

[0092] Step A1, take 200 μL of spiked sample containing 5-HT and its metabolites, add it to 20 μL of internal standard working solution; then add 400 μL of pH buffer solution, vortex mix for 1 min, and obtain a pre-treated solution; Step A2, selecting samples Example 6-1, Example 6-4, Example 7-1, Example 7-5 and commercially available adsorption microspheres from the zwitterionic ion exchange microsphere samples prepared in Example 6 and Example 7 as fillers in the solid phase extraction process, taking 3 mg of each, adding them to a 96-well solid phase extraction plate, taking 600 μL of methanol and adding it to the solid phase extraction plate for activation, and pressing dry with a positive pressure meter to control the flow rate; then adding 600 μL of deionized water to balance the solid phase extraction plate, and pressing dry with a positive pressure meter to control the flow rate; Step A3, take 600 μL of the prefabricated treatment solution obtained in step A1, add it to the solid phase extraction plate, and press it dry with a positive pressure instrument to control the flow rate; rinse with 600 μL of deionized water and 600 μL of methanol solution in sequence, and press it dry with a positive pressure instrument to control the flow rate; Finally, 200 μL of 2% formic acid-methanol solution was added for elution, and the eluate was collected in a 96-well collection plate, and the flow rate was controlled by a positive pressure instrument to press dry; the collected eluate was blown dry under nitrogen, and 100 μL of deionized water was added for reconstitution; Step A4, high performance liquid chromatography tandem mass spectrometry analysis, using a chromatographic column of Phenomenex Kinetex F5 (2.6 μm, 3.0×100 mm), a chromatographic column temperature of 35° C., an injection volume of 10 uL, mobile phase A of 0.1% formic acid aqueous solution, mobile phase B of methanol solution, and elution according to the gradient parameters in Table 10: Table 10 Gradient parameters

[0093] The recovery rates of each group of fillers for 5-hydroxytryptamine and its metabolites are shown in Table 11 below: Table 11 Determination of the recovery rates of 5-HT and its metabolites by the above five groups of microspheres

[0094] like Fig. 9 According to the selective adsorption principle shown, the zwitterionic ion exchange microspheres provided by the present invention, because they contain both carboxyl functional groups and quaternary ammonium functional groups, can achieve the simultaneous recovery of acidic analytes and alkaline analytes, and both can achieve a high recovery rate. As can be seen from Table 11, when the carboxyl density in the microspheres is high, the recovery rate of the alkaline analyte 5-hydroxytryptamine is significantly improved; when the quaternary ammonium density in the microspheres is high, the recovery rate of 5-hydroxyindoleacetic acid is significantly improved. On the other hand, it can also be seen from Table 11 that commercially available adsorption microsphere materials can only separate and recover alkaline analytes, while the zwitterionic ion exchange microspheres provided by the present invention not only have a high recovery rate for alkaline analytes, but also have a high recovery rate for acidic analytes.

[0095] In summary, by simultaneously introducing carboxyl functional groups and quaternary ammonium functional groups into the porous microsphere structure, the amphoteric ion exchange microsphere adsorption material provided by the present invention has the ability to efficiently and simultaneously recover acidic analytes and alkaline analytes; in addition, because it has a benzene ring structure and a large amount of charge attached to the surface, the amphoteric ion exchange microsphere provided by the present invention also has the ability to efficiently and simultaneously recover polar and non-polar analytes, and has a high material retention. The amphoteric ion exchange microsphere adsorption material provided by the present invention is particularly suitable for the simultaneous recovery and adsorption of acidic analytes and alkaline analytes, and can effectively solve the technical problem that two fillers and two adsorption and desorption steps are required in the prior art to recover and measure.

[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A zwitterionic ion exchange microsphere adsorption material, characterized in that: The microsphere adsorption material contains quaternary ammonium functional groups and carboxyl functional groups; The structural formula of the microsphere adsorption material is as follows: 。 2. The microsphere adsorption material according to claim 1, characterized in that: The density of the quaternary ammonium functional group is 0.5-2 mmol / g; The density of the carboxyl functional group is 1-5 mmol / g.

3. The microsphere adsorption material according to claim 1, characterized in that: The particle size of the microsphere adsorption material is 10μm-300μm; The pore size of the microsphere adsorption material is 1 nm-50 nm.

4. A method for preparing the microsphere adsorption material according to any one of claims 1 to 3, characterized in that: The specific steps are as follows: Step 1, adding a dispersant to distilled water, and stirring thoroughly to obtain a dispersant aqueous solution with a concentration of 0.1%-20%; Step 2, weighing 50-90 parts of a polymer monomer mixture, 1-90 parts of a porogen, and 0.003-1 parts of an initiator according to their mass fractions, and stirring them thoroughly to obtain 100 parts of an oil phase mixture; The polymer monomer mixture includes a first monomer and a second monomer; The first monomer is selected from o-divinylbenzene, m-divinylbenzene, and p-divinylbenzene; The second monomer is selected from p-chloromethylstyrene and 4-chlorostyrene; Step 3, fully mixing the acrylic acid ester monomer with the oil phase mixture and the dispersant aqueous solution, and reacting under condensation reflux at 50-80° C. for 4-20 hours; after the reaction, cooling to room temperature, washing with water and ethanol in turn, and drying at 60° C. for 10-12 hours to obtain a first reaction product; The acrylic acid ester monomer is selected from methyl acrylate, methyl methacrylate, and ethyl methacrylate; The added mass of the acrylic ester monomer is 1%-20% of the polymer monomer mixture; The mass ratio of the oil phase mixture to the dispersant aqueous solution is (30-60):100; Step 4, placing the first reaction product in a toluene solution and swelling it for 0.5-1.5 hours to obtain a swollen mixture; Adding a tertiary amine monomer to the swelling mixture, and continuing to stir and react at 80-90° C. for 4-20 hours, and obtaining a second reaction product after the reaction is completed; The tertiary amine monomer is selected from N,N-dimethylbutylamine, trimethylamine, and triethylamine; The amount of the tertiary amine monomer added is 1-10 times the mass of the second monomer; Step 5, adding an alkaline methanol solution to the second reaction product, stirring at a low speed at 65-75° C., and performing an ester hydrolysis reaction for 20-30 hours; After the reaction is completed, the mixture is cooled to room temperature, washed with ethanol, sodium bicarbonate solution and water in turn, and dried to obtain the zwitterionic ion exchange microsphere adsorption material.

5. The preparation method according to claim 4, characterized in that: The dispersant in step 1 is hydroxypropyl methylcellulose and / or polyvinyl alcohol.

6. The preparation method according to claim 4, characterized in that: In step 2, the mass ratio of the first monomer to the second monomer is 1:(1-3).

7. The preparation method according to claim 4, characterized in that: The porogen in step 2 is a mixture of one or more of dichloromethane, n-dodecane, toluene, o-dichlorobenzene, and liquid paraffin; The initiator is azobisisobutyronitrile and / or benzoyl peroxide.

8. The preparation method according to claim 4, characterized in that: The specific steps of fully mixing in step 3 are: adding the acrylic ester monomer and the oil phase mixture into the dispersant aqueous solution and stirring evenly; Alternatively, the oil phase mixture is first added to the dispersant aqueous solution, and then the acrylic acid ester monomer is added at 50-80° C. and mixed evenly.

9. The preparation method according to claim 4, characterized in that: The stirring rate in step 1 and step 2 is 200-500 r / min; The rate of low-speed stirring in step 5 is 80-120 r / min.

10. A solid phase extraction device for simultaneous separation of acidic and basic analytes, characterized in that: The amphoteric ion exchange microsphere adsorption material described in any one of claims 1 to 3 or the amphoteric ion exchange microsphere adsorption material prepared by the method described in any one of claims 4 to 9 is used as filler.

Citation Information

Patent Citations

  • Composite anion exchange membrane preparation method

    CN103881132A